Using E-learning technologies to bridge the gap between international entrepreneurship education and practice - Hegarty, Cecilia; Bell, Jim; Loane, Sharon (Senate Hall, 2010)
This paper seeks to address the emergent needs of international entrepreneurship scholars and in doing so it aims to identify the needs of international firms operating in culturally dynamic market spaces. The paper conceptually deals with evolution within the disciplines associated with international entrepreneurship and in particular the development of E-learning technologies to deliver entrepreneurship education. Adopting innovative technology that allows for flexible learning is not only critical for educational institutions in striving to cope with changes in the education landscape but also an effective means for international firms to transfer entrepreneurial knowledge. Thus, E-learning offers a means of bridging the gap between entrepreneurship education and practice.
Keywords: e-learning|entrepreneurship education